The credit saving cooperative`s contribution to the Mexican local development - Lara Gómez, Graciela; Rico Hernández, Amalia (REVESCO. Revista de Estudios Cooperativos, 2011)
From an empiric and theoretical approach to the social enterprises and its role at the local development, it was sought to establish how the credit and saving cooperatives are a pertinent strategy for the economic and social advance from the Mexican communities. For this purpose the qualitative method was used to utilize the study case strategy; it were selected four organizations located in classified areas as high marginalization according to the official Mexican indicators. The cases are cooperatives founded with the participation from members of the Catholic Church and whose financial activity has being fundamental at their local scope. The results demonstrate that the organization of cooperatives, the voluntary action from his members and in some cases the state support are effective tools at the local development promotion. The main benefits for the members are translated in the grant credits and additional services as educative scholarships and health services. It was verified that with the practice of the principles and cooperatives values facilitate the teamwork and the members develop entrepreneurial skills and directives that individually and collectively benefits them, improving their quality of life.